Influência do ambiente térmico e de diferentes dietas na superovulação e nos parâmetros fisiológicos de ovelhas Santa Inês - Marcio Gianordoli Teixeira Gomes (2011)
This review aims to study and review factors of strong influence on superovulation in Santa Ines ewe, as well as to verify the effects exerted by the supplementation with polyunsaturated fatty acid and heat stress on the reproduction of these animals. It can be verified that the heat stress provides a strong impact on animal breeding and the use of fatty acids in animal feed can minimize the effect of heat stress on this variable. Moreover, it was observed that inconsistent results on the results of the use of superovulation protocol on Santa Ines ewe can still be found, being listed several factors involved, such as the hormone utilized, time of follicular wave at the beginning the protocol, nutrition, climate, among others